Reflexões de professoras de sala de aula sobre os “casos” de seus estudantes com deficiência intelectual: implicações para inclusão produzidas no contexto de uma pesquisa colaborativa - Sousa, Fabiana Maria Barbosa de (2024)
This research aimed to analyze the process involved in the systematization and analysis of cases of students with intellectual disabilities, written by regular classroom teachers about their students, in the context of collaborative research, considering the possibilities of building inclusive practices. As specific objectives Understand how inclusive practices are constructed based on the identification of the elements that provoke the systematization and analysis of the case of a student with intellectual disability prepared by the teachers in the common classroom themselves. Identify the knowledge about inclusion, pedagogical practices and learning of students with disabilities that emerge and/or are required in the systematization and analysis of the case that emerged throughout the research meetings. The theoretical framework is based on Vygotsky's Historical-Cultural assumptions that support the understanding of the development and learning of people with intellectual disabilities. The research was also based on the principles that deal with inclusive education anchored in several authors such as Figueiredo, Mantoan, Lanuti and Lustosa, among other national and international researchers. The collaborative qualitative research followed specific scripts for data collection (questionnaires, reflective scripts, recordings of central ideas in texts and videos). Nine teachers from the Fortaleza municipal education network, who had students with intellectual disabilities in their classrooms, participated in this research. The research included seven systematic and face-to-face meetings with the participating teachers where studies on intellectual disability, inclusion, pedagogical practices were proposed, as well as the cases of students with intellectual disabilities written by the teachers were discussed and analyzed collectively. Among the research results, we can highlight the presence of conceptual misunderstandings about intellectual disability both in the teachers' speeches and in the case reports. There was also a misunderstanding regarding the understanding of inclusion in its practice in the classroom, similar to the concepts of integration and the principles of segregation. Another aspect evident in the teachers' speeches and in the students' cases was the fragility of continued training on this topic with regular classroom teachers. Throughout the research meetings, the analysis and discussion of cases of students with intellectual disabilities written by the teachers proved to be an important methodology in the training process, involving inclusive themes. That said, it is considered that the methodology used in the research may have promoted conceptual expansion on inclusion, learning for students with intellectual disabilities and pedagogical practices on the part of the participating teachers.